Techno-Economic Aspects of Solid Food Wastes into Bio-Manure - Dr. Rajeev Singh; Er. Vipin Kumar Verma; Er. Dileep Kumar Verma (International Journal of Engineering and Management Research, 2022)
Solid waste is health hazard and cause damage to the environment due to improper handling. Solid waste comprises of Industrial Waste (IW), Hazardous Waste (HW), Municipal Solid Waste (MSW), Electronic waste (E-waste), Bio-Medical Waste (BMW) which depend on their supply & characteristics. Food waste or Bio-waste composting and its role in sustainable development is explained in food waste is a growing area of concern with many costs to our community in terms of waste collection, disposal and greenhouse gases. When rotting food ends up in landfill it turns into methane, a greenhouse gas that is particularly damaging to the environment. Composting is biochemical process in which organic materials are biologically degraded, resulting in the production of organic by products and energy in the form of heat. Heat is trapped within the composting mass, leading to the phenomenon of self-heating.This overall process provide us Bio-Manure. Keywords: environment ,sustainable development ,food waste, Bio-Manure